Productivity, yield attributes and phenology of wheat (Triticum aestivum L.) under different sowing environments under central Punjab - Ram, Hari; Gupta, Neha (Journal of Cereal Research, 2016)
The field experiment was conducted at the Punjab Agricultural University, Ludhiana during the rabi 2011-12 and 2012-13. The experiment was conducted in split plot design keeping two dates of sowing, viz., 12 December and 5 January in main plots and five varieties, viz., HD 3059, WH 1021, DBW 71, PBW 590 and PBW 373 as sub-plots with three replications. Under late sown conditions, yield attributes, days to earing and physiological maturity, biological as well as grain yield and pheno-thermal index were significantly higher than under very late sown conditions. PBW 373 accumulated higher GDD, HTU and PTU than other varieties on pooled basis at earing and maturity. Wheat variety HD 3059 recorded the highest grain yield which was statistically at par with DBW 71. The grain yield recorded in variety HD 3059 in 2012-13 under late sown conditions was only statistically at par with PBW 373 and DBW 71 but significantly better than all the varieties sown at two different times during both years. The lowest grain yield was recorded in PBW 373.